Release currents of IP₃ receptor channel clusters and concentration profiles - Thul, Ruediger; Falcke, Martin (Biophysical Society, 2004)
We simulate currents and concentration profiles generated by Ca2+ release from the endoplasmic reticulum (ER) to the cytosol through IP3 receptor channel clusters. Clusters are described as conducting pores in the lumenal membrane with a diameter from 6 nm to 36 nm. The endoplasmic reticulum is modeled as a disc with a radius of 1–12 mm and an inner height of 28 nm. We adapt the dependence of the currents on the trans Ca2+ concentration (intralumenal) measured in lipid bilayer experiments to the cellular geometry. Simulated currents are compared with signal mass measurements in Xenopus oocytes. We find that release currents depend linearly on the concentration of free Ca2+ in the lumen. The release current is approximately proportional to the square root of the number of open channels in a cluster. Cytosolic concentrations at the location of the cluster range from 25 μM to 170 μM. Concentration increase due to puffs in a distance of a few micrometers from the puff site is found to be in the nanomolar range. Release currents decay biexponentially with timescales of < 1 s and a few seconds. Concentration profiles decay with timescales of 0.125–0.250 s upon termination of release.